Integrated solar energy systems for rural electrification in Kenya - Rabah, KVO (Pergamon-Elsevier Science Ltd, 2005)
In sub-Saharan Africa where population is projected to increase by 124% in the next 20 years, grid extension has advanced more slowly than in any other major regions; only about a third of the urban residents, and a mere 8% of the rural population, are served by grid electricity. Today, it is estimated that nearly two billion people worldwide remain without access to electricity or the immediate prospect of grid electrification. The situation in Kenya is no different. About 80% urban and 99.5% rural households, respectively, in Kenya have no access to electricity and its services. The annual electricity demand currently stands at 6% and increasing. However, we have shown that Kenya is well endowed with abundant renewable energy (RE) potential, especially solar energy resources. In our study, we have observed that Kenya gets an annual average exposure to sunshine of about 10 Ih per day in most regions, and an annual mean radiation of 6.98 kW h/m(2), which if harnessed efficiently could contribute to improve quality of life in rural and poor urban sector in Kenya. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: Models